In search of the real Pseudomallada prasinus (Neuroptera, Chrysopidae) - Duelli, Peter; Obrist, Martin K. (Zootaxa, 2019)
Three sympatric morphs of Pseudomallada prasinus (Burmeister, 1839) were hybridized in search of reproductively     separated species. In addition, 26 morphological and biological traits were recorded for living and preserved specimens of the three morphotypes.                                                                                                         Cross-breeding experiments showed that the prasinoid morph “marianus” is a different species from either the “greenhead” or “sulfurhead” morphs. All three are morphologically and biologically distinct. “Greenhead” and “sulfurhead” are small to medium sized and deposit eggs singly, without obligatory diapause in the second instar. In most specimens of these two smaller “prasinus” morphs there is a red or brown suture below the antennae, which can fade with age or preservation. P. “marianus” is a large species, depositing bundled eggs, with an obligatory diapause in about half of the L2. In none of the collected or reared P. “marianus” was a red or brown suture below the eyes observed. The forewing sizes of the type specimens of Chrysopa prasina Burmeister, 1839, C. coerulea Brauer, 1851, and C. marianus Navás, 1915 differ significantly from those of C. aspersa Wesmael, 1841 and other, later synonymized type specimens such as C. sachalinensis Matsumura, 1911, C. burri Navás, 1914, C. caucasica Navás, 1914, or C. vernalis Navás, 1926. This strongly suggests that the “marianus” morph is the real P. prasinus and the “greenhead” and “sulfurhead” morphs correspond to P. aspersus or one of the later synonymized species with smaller wing size.Pseudomallada marianus (Navás, 1905) is confirmed as a synonym of P. prasinus, depositing bundled eggs, whereas smaller prasinoid morphs, depositing single eggs, are not P. prasinus—and are morphologically distinct from P. abdominalis (Brauer, 1856). Pseudomallada aspersus (Wesmael, 1841) is a valid species, but at this point it is not possible to assign it to one of the prasinoid morphs because most of the live color traits are not discernible in old type specimens. A diagnostic description of the “real” P. prasinus can separate almost all P. prasinus specimens, even in museum collections, from P. aspersus (likely to be the “greenhead” morph) and the Mediterranean “sulfurhead”.